Post Secondary educators can increase educational reach with Universal Design for Learning - Coy, Kimberly (Educational (Re)naissance, 2017)
Meeting the needs of a variety of learners in college and university settings is of vital importance. By designing courses infused with Universal Design for Learning (UDL) principles, guidelines and checkpoints; professors and instructors create environments targeted toward meeting the educational needs of a wider variety of students. UDL works most effectively at the design stage. This paper aims to support learning environment design by presenting ten specific strategies for infusing UDL within post-secondary courses at the university level. These strategies will include: identifying barriers to learning, alternatives for participating during class time, effective alternative assessments based on construct relevance and UDL meta cognitive goals and transparency.